A CLINICAL AND HISTOPATHOLOGICAL STUDY OF CICATRICIAL ALOPECIA - Neerja Puri; Asha Puri (Our Dermatology Online, 2013)
Introduction: Cicatrical alopecia occurs in otherwise healthy men and women of all ages and is seen worldwide Material and Methods: A study of 40 patients was conducted to study the clinical variants and histopathology of cicatricial alopecia. Results and Discussion: n our study, it was seen that maximum number of cases of cicatrical alopecia were of LPP (27.5%) followed by 25% of DLE, 20% patients had pseudopelade of Brocq, SLE was seen in 5% cases followed by Scleroderma, dermatomyositis, Keratosis follicularis spinulosa decalvans, aplasia cutis, kerion, follicular mucinosis, pemphigus, dissecting cellulitis of scalp/ pyogenic folliculitis and acne keloidalis nuchae in 2.5% cases each. Regarding the morphology of lesions,epidermal atrophy was seen in 90% patients, erythema was seen in 55% cases, follicular pluging was seen in 40% patients, telangiectasias in 27.5% patients, diffuse scaling in 25% patients and mottled hyperpigmentation was seen in 20% patients. In our study, commonest histopathological feature of alopecia was perifollicular fibrosis seen in 65% patients, basal cell vacuolization was seen in 52.5% patients,perifollicular lymphocytic infiltrate were seen in 50% patients, epidermal atrophy seen in 35% patients and hyperkeratosis was seen in 20% patients.